"Woman's face" of unstable angina - A. G. Gurchenok; S. A. Okrugin; Yu. I. Zyablov; A. A. Garganeeva (Российский кардиологический журнал, 2007)
The authors compare unstable angina clinical course, short- and long-term prognosis in working-age male and female residents of Tomsk City. Short- and long-term prognosis is better in female patients with unstable angina than in their male peers. Factors associated with unstable angina incidence include diabetes mellitus in women and previous myocardial infarction in men.